2021
DOI: 10.3389/fphar.2021.687095
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Attenuates Non-Alcoholic Fatty Liver Disease by Enhancing Energy Expenditure and Regulating Autophagy via AMPK

Abstract: Background: The prevalence of non-alcoholic fatty liver disease (NAFLD) keeps growing recently.Purpose: To investigate the effects and mechanisms of naringenin (NAR) on NAFLD.Methods: High-fat diet (HFD)-induced NAFLD rats were orally administered with NAR at 10, 30, and 90 mg/kg for 2 weeks. The serum level of triglyceride (TG), total cholesterol (TC), glutamic-oxaloacetic transaminase (AST), and glutamic-pyruvic transaminase (ALT) was measured. The hepatic histology was detected by H&E and oil red O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…An in silico previous study reported that kaemferide is a promising AMPK activator [ 8 ]. Naringenin has shown an anti-adipogenic effect by binding to the AMP binding sites of the γ-subunit as the agonists of AMPK [ 9 ]. In the present study, molecular docking analysis showed that the flavonoids activate AMPK directly as positive modulators by interacting with the R groups of the CBS domains in the γ-subunit of AMPK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in silico previous study reported that kaemferide is a promising AMPK activator [ 8 ]. Naringenin has shown an anti-adipogenic effect by binding to the AMP binding sites of the γ-subunit as the agonists of AMPK [ 9 ]. In the present study, molecular docking analysis showed that the flavonoids activate AMPK directly as positive modulators by interacting with the R groups of the CBS domains in the γ-subunit of AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…AMP binding to the γ-subunit stimulates Thr172 phosphorylation by the upstream kinases, including liver kinase B1 (LKB1) and calcium/calmodulin-dependent protein kinase kinase-β (CaMKKβ) [ 7 ]. Various in silico studies showed that polyphenols act as positive modulators by interacting with the γ-subunit of AMPK, similar to AMP [ 8 9 ]. Accordingly, a direct activator of AMPK that would mimic the mechanism of AMP might be a suitable therapeutic strategy against adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Group A (Control: normal saline), Group B (Naringin at 30 mg/kg BW intraperitoneally), Group C (Naringin at 30 mg/kg BW and Vanadium at 10mg/kg BW), Group D (Vanadium at 10mg/kg BW intraperitoneally). The duration of the experiment was 14 days [7] , [8] .…”
Section: Methodsmentioning
confidence: 99%
“…NAR has also been shown to exert hepatoprotective effects in vivo [ 42 , 65 ] that can prevent the development of MAFLD, which is frequently associated with obesity and MetS. Such effects focus on decreasing hepatic enzyme activity and hindering TG and cholesterol deposits, which can be macroscopically and histologically evident [ 66 ].…”
Section: Effects Of Naringenin Against the Various Components Of Obesitymentioning
confidence: 99%
“…Most in vivo and in vitro studies describe a dose-dependent effect of NAR [ 19 , 42 , 87 ], still, its use has been studied in vivo at low doses (25 mg/kg body weight) [ 19 ] in a short period of time (2 days, intraperitoneal) [ 102 ] with positive results (see Table 1 ), which may support its use as a dietary supplement [ 65 ]. It is also important to consider that the documented effects regarding NAR are mainly preventive, protective and related to an improvement, but are not curative.…”
Section: The Hunger–satiety Pathwaysmentioning
confidence: 99%